PENGARUH KEMUDAHAN, KEAMANAN, KEPERCAYAAN GEN MILENIAL DAN GEN Z TERHADAP MINAT MELAKUKAN TOP UP E-MONEY MELALUI TOKOPEDIA - Yuniar Basuki, Nanda; Hasanah, Nurul (Yayasan Education and Social Center, 2024)
This research is motivated by the issue that, despite Tokopedia becoming the second largest e-commerce platform in 2023, public interest in using the e-money top-up feature provided by Tokopedia does not align with the number of Tokopedia app users. This is evidenced by a pre survey showing that the feature still has relatively low interest. The purpose of this research is to determine the influence of ease of use, security, and trust on the interest in using the e-money top-up feature through Tokopedia. The study utilizes a questionnaire with a sample size of 100 respondents who are users of the e-money top-up feature on the Tokopedia app. The analysis method used in this research is multiple linear regression, employing the SPSS 26.0 program. The results of this study indicate that the variables of ease of use, security, and trust partial and simultaneous, have a positive and significant impact, on the interest in using the e-money top-up feature through Tokopedia. The findings of this research are expected to be beneficial for Tokopedia, providing additional information, input, and suggestions to help increase public interest in using the e-money top-up feature through Tokopedia.